2017
DOI: 10.3390/md15030077
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fucoidan on Aβ25–35 and d-Gal-Induced Neurotoxicity in PC12 Cells and d-Gal-Induced Cognitive Dysfunction in Mice

Abstract: Alzheimer’s disease (AD) is a chronic neurodegenerative disease which contributes to memory loss and cognitive decline in the elderly. Fucoidan, extracted from brown algae, is a complex sulfated polysaccharide and potential bioactive compound. In this study, we investigated whether fucoidan protects PC12 cells from apoptosis induced by a combination of beta-amyloid 25–35 (Aβ25–35) and d-galactose (d-Gal), and improves learning and memory impairment in AD model mice. The results indicated that fucoidan could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 33 publications
(32 reference statements)
6
58
0
Order By: Relevance
“…In the current study, Aβ 25-35 was used to induce SH-SY5Y cells at different concentrations. The results revealed a marked decrease in cell viability with increased Aβ 25-35 concentrations, which is consistent with the results of previous studies (21,22). To avoid adverse effects following induction, 30 µM of Aβ [25][26][27][28][29][30][31][32][33][34][35] (with a cell viability of 63.4%) was selected for subsequent cell-based in-vitro experiments.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, Aβ 25-35 was used to induce SH-SY5Y cells at different concentrations. The results revealed a marked decrease in cell viability with increased Aβ 25-35 concentrations, which is consistent with the results of previous studies (21,22). To avoid adverse effects following induction, 30 µM of Aβ [25][26][27][28][29][30][31][32][33][34][35] (with a cell viability of 63.4%) was selected for subsequent cell-based in-vitro experiments.…”
Section: Discussionsupporting
confidence: 87%
“…Major sulfated polysaccharides found in marine algae include fucoidan from brown seaweed, ulvan from green seaweed, and carrageenan from red seaweed. Several studies have reported on the neuroprotective effect of fucoidan in various neurodegeneration models [209][210][211][212][213][214]. Luo et al's study [209] demonstrated that fucoidan, isolated from Laminaria japonica, attenuated MPTP-induced locomotor activity deficits, prevented depletion of striatal dopamine and its metabolite, dihydroxyphenylacetic acid (DOPAC) level, reduced loss of dopaminergic neurons and tyrosine hydroxylase protein expression, and attenuated the increase of lipid peroxidation level and decreases of antioxidant enzyme activities as well as total antioxidant capacity in the substantia nigra pars compacta of MPTPinduced mice.…”
Section: Marine Macroalgae (Seaweeds)mentioning
confidence: 99%
“…Heart, liver, spleen, lung, kidney, and brain tissue were collected and homogenized. Tissue homogenate and plasma were added with 0, 0.2, 0.4, 0.8, 1, 2, 4, 6,8,10,15,20,25,30,35,40,45,50,60,80 and 100 µL of FITC solutions respectively to obtain FITC-tissue homogenate mixture. The fluorescence intensity was measured at 490 nm and 520 nm using a microplate reader.…”
Section: Tissue Distribution Of Fucoidan In Micementioning
confidence: 99%
“…The SO4 2− is the main functional group responsible for the biological properties of polysaccharides, and its quantity and position are critical determinants of the activity of these macromolecules. Recent studies have shown that fucoidan can exert a wide range of pharmacological effects, including anti-inflammatory [6], antitumor [7], antioxidative [8], antiviral, and antithrombotic activity, as well as improving immune response and lipid metabolism [5,[9][10][11][12]. However, only a small number of studies addressed the mechanism of absorption and tissue distribution of this compound in vivo given their high molecular size [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%